Tribological behaviour of TiO2 Atmospheric Plasma Spray (APS) coating under mixed and boundary lubrication conditions in presence of oil containing MoDTC. (February 2018) - Deshpande, P.; Minfray, C.; Dassenoy, F.; Thiebaut, B.; Le Mogne, Th.; Vacher, B.; Jarnias, F.
Abstract: Tribological behaviour of steel APS coating and TiO2 APS coating was investigated and compared with reference steel material under boundary lubrication in presence of MoDTC. Significant friction and wear reduction was observed in case of TiO2 APS coating compared to conventional steel and steel APS coating. This was due to the formation of pure MoS2 in the form of long crystalline flakes directly attached to TiO2 substrate. Friction was slightly higher in case of steel since Mo-oxysulphide formation was observed along with some MoS2 flakes embedded in an amorphous matrix. Effect of roughness and addition of ZDDP on MoDTC decomposition mechanism was discussed. Tribocatalytic effect was proposed to explain the complete decomposition of MoDTC in steel/TiO2 APS contact. Highlights: Significant friction reduction observed in case of steel/TiO2 APS contact compared to reference steel/reference steel. Friction reduction was due to formation of long, crystalline MoS2 flakes directly attached to the TiO2 substrate. Complete decomposition of MoDTC in steel/TiO2 APS contact related to a tribocatalytic process. Low wear obtained for TiO2 APS due to sub-stoichiometric oxide (Tin O2n-1 ) as Magneli phases.